2019
DOI: 10.1002/phar.2344
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Taxane‐Containing Regimens for Treatment of HER2‐Negative Metastatic Breast Cancer: A Network Meta‐analysis

Abstract: STUDY OBJECTIVES To compare the effectiveness of different taxane-containing regimens and to identify the best strategy for the treatment of human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (MBC). DESIGN Network meta-analysis of 20 randomized controlled trials (RCTs). PATIENTS A total of 6577 patients with HER2-negative MBC who received treatment (20 different regimens) with taxanes (paclitaxel [4267 patients] or docetaxel [2310 patients]). MEASUREMENTS AND MAIN RESULTS The Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Paclitaxel/capecitabine/BEV was reported as the most effective combination in two meta-analyses of BEV in mBC. These analyses included 16 and 20 randomized controlled trials of BEV in different lines of treatment [ 21 , 22 ]. This is in contrast to our analysis, according to which there was no difference in efficacy between taxane monotherapy and taxane-based chemotherapy combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel/capecitabine/BEV was reported as the most effective combination in two meta-analyses of BEV in mBC. These analyses included 16 and 20 randomized controlled trials of BEV in different lines of treatment [ 21 , 22 ]. This is in contrast to our analysis, according to which there was no difference in efficacy between taxane monotherapy and taxane-based chemotherapy combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also found that paclitaxel-based combinations were more effective than paclitaxel alone for efficacy in ORR, which is similar to the case of capecitabine in our analysis. Further improvement in OS was associated with the taxane combination regimens – evidence which motivated us to embark on the current analysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…About 5-10% of breast cancer patients have metastatic disease, while 20-40% of early breast cancer patients eventually develop metastatic breast cancer [1]. Advanced tumors, especially HER2-negative metastatic breast cancer, are generally considered to be incurable despite the continuous development of therapeutic drugs [2][3][4]. Te prognosis of metastatic breast cancer is also relatively poor.…”
Section: Introductionmentioning
confidence: 99%
“…The median survival period of patients is only 2-3 years, and the 5-year survival rate is 23–26%. Therefore, metastatic breast cancer remains a major medical challenge [ 4 ]. For HER2-negative local recurrent or metastatic breast cancer, the first-line treatment options in Europe include single-agent chemotherapy and bevacizumab combined with chemotherapy drugs (paclitaxel or capecitabine).…”
Section: Introductionmentioning
confidence: 99%